2010
DOI: 10.1017/s174413311000006x
|View full text |Cite
|
Sign up to set email alerts
|

Choice cuts: parsing policymakers’ pursuit of patient empowerment from an individual perspective

Abstract: In this commentary I explore several ways in which the psychology of individual decision-making shapes consumers' choices in medical settings and the potential for choice-based policies to improve the performance of the health care system. This analysis draws some crucial distinctions among the various pathways though which policymakers expect choice to improve outcomes and the various forms of support that might enhance patients' engagement with choice. I also consider how choice-promoting policies interact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 81 publications
0
39
0
Order By: Relevance
“…For these beneficial outcomes, choice needs to be available and to be exercised. The United States is perhaps the country with most consumer-oriented arrangements for health care, and, for those with insurance coverage, there is choice of both health plan and provider, although choice of the former has implications for the choice of the latter (Schlesinger, 2010). A systematic review of the US literature has found mixed evidence of the impacts of public reporting on both kinds of choices (Fung et al, 2008).…”
Section: Choicementioning
confidence: 99%
See 1 more Smart Citation
“…For these beneficial outcomes, choice needs to be available and to be exercised. The United States is perhaps the country with most consumer-oriented arrangements for health care, and, for those with insurance coverage, there is choice of both health plan and provider, although choice of the former has implications for the choice of the latter (Schlesinger, 2010). A systematic review of the US literature has found mixed evidence of the impacts of public reporting on both kinds of choices (Fung et al, 2008).…”
Section: Choicementioning
confidence: 99%
“…This special issue also includes a paper that explores a complication for governments from legal challenges to policies that restrict publicly financed choice, judges' decisions on individual cases may have far-reaching systemic consequences (in the European Union (EU) and Canada; Flood and Haugan, 2010); and a commentary that explores the implications of the fraught and complex nature of choices between insurers and providers of health care for designing effective choice policies (Schlesinger, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gatekeeping systems are expected to improve efficiency, quality and equality and to contain costs, with potential drawbacks for patient autonomy. Provider choice, on the other hand, is seen as a measure to empower patients and improve quality, but many scholars predict increased levels of inequalities due to individuals' varying capacities to make informed choices (Coulter, 2010;Hanoch and Rice, 2010;Schlesinger, 2010).…”
Section: Review Of Existing Research: Consequences Of Gatekeeping Andmentioning
confidence: 99%
“…When choosing specialists and hospitals, most people prefer being advised by, or even leaving the choice to their GP (Berendsen et al, 2009). In terms of the choice of healthcare provider, evidence indicates the paradoxical situation, that individuals like having choice but choose not to use it (Coulter, 2010;Schlesinger, 2010). With respect to choosing the level of care and gatekeeping restrictions, evidence indicates that most patients appreciate the role of a family physician 1 as the first point of contact and coordinator of care (Berendsen et al, 2009;Grumbach et al, 1999;Himmel et al, 2000).…”
Section: Patient Empowerment and Patient Satisfactionmentioning
confidence: 99%
“…[2][3][4][5] Bounded rationality suggests that in making decisions, individuals are often constrained by both the limits of their cognitive capacity to process information as well as by the time and attention they have for any given decision. This view contrasts with the neoclassic economic model of consumer behavior, which assumes that people seek out and consider all available data to inform their choices and easily trade off the advantages and risks of each choice in a rational way.…”
Section: Conceptual Foundationsmentioning
confidence: 99%